Use of Wearable Technology in Improving Children's Health: Implementation and Impact on Healthy Lifestyles - Haryanto Nugroho (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
Wearable technologies, such as smartwatches and fitness trackers, have gained popularity in recent years as tools for monitoring health. These devices are increasingly used not only by adults but also by children, offering a promising approach to promoting healthy living habits. This study investigates the impact of wearable technology on improving healthy living habits in children, specifically focusing on physical activity levels and dietary behaviors. The research employed a quasi-experimental design and involved 150 children aged 8 to 12 years who wore wearable devices to track their physical activity over a 6-month period. The data was collected through physical activity measurements, dietary assessments, and healthy lifestyle surveys conducted both before and after the intervention. The results demonstrated a significant increase in the children's physical activity levels, with a notable reduction in sedentary behaviors such as prolonged sitting. Furthermore, children using wearable technology showed improvements in their dietary choices, opting for healthier food options more frequently. Parents also reported a positive change in their children’s attitudes towards health, with an increased awareness of the importance of maintaining a healthy lifestyle. These findings suggest that wearable technology can be an effective tool in promoting physical activity and healthy eating habits among children. The study highlights the potential of integrating such technologies into children's health education to support the development of better lifestyle behaviors. Given the positive outcomes observed, it is recommended that policymakers, educators, and health professionals consider incorporating wearable devices into public health initiatives aimed at improving children’s health and well-being. Further research could focus on long-term effects and explore additional benefits of wearable technology in enhancing various aspects of child development.